FAKTOR-FAKTOR YANG MEMPENGARHI EKSPOR KOMODITI INDONESIA - Hena, Eduardus (Journal of Information System, Applied, Management, Accounting and Research, 2024)
This research aims to determine the effect of inflation and the Rp/USD exchange rate on Indonesian commodity exports. The type of data used in this research is secondary data in a time series for three years from January 2021 to December 2023. The data is sourced from the official website of the Central Bureau of Statistics for Indonesian Commodity Exports, and sourced from Bank Indonesia publications for Domestic inflation data and IDR/USD exchange rate. The data analysis method in this research is multiple linear regression and hypothesis testing partially using the t test and simultaneously using the F test. The results of the research show that partially domestic inflation does not have a significant effect on Indonesian commodity exports, the Rp/USD exchange rate has a significant effect on commodity exports. Indonesia. Apart from that, together domestic inflation and the Rp/USD exchange rate have a significant effect on Indonesian commodity exports.